Analysis of the Production Area Planning of Ground Fish at CV Hadori in East Lampung District - Azzahra, Amalya Almira; Rr. Erlina; Ambarwati, Dwi Asri Siti (Asian Journal of Applied Business and Management, 2024)
This study investigates production scale planning at CV Hadori, a fish processing company, using Break-Even Point (BEP) analysis and linear trend forecasting. The company faces significant overproduction of minced fish, leading to excess inventory and reduced profits. The research employs a descriptive quantitative approach, analyzing historical production and sales data through trend analysis and BEP calculations. Findings indicate that CV Hadori must produce and sell over 405,436 kg of processed fish in 2026 to achieve profitability. Recommendations include optimizing production and sales strategies, investing in appropriate machinery, and continuously monitoring market conditions to adjust forecasts. Effective production planning will help minimize surplus, enhance profitability, and ensure long-term sustainability.